Decision Making Method to Optimal Selection of Area for Building Project Based on Fuzzy Parameterized Neutrosophic Soft Expert Set - Ihsan, Muhammad (Yugoslav Journal of Operations Research; Online first, 2025)
Fuzzy parameterized neutrosophic soft expert sets is a useful extension of fuzzy parameterized intuitionistic fuzzy soft expert and neutrosophic soft sets. This set deals with attributes as well but with many definitive assessments, whereas the soft set only addresses one set of attributes. The development of this model addresses the limitations of existing soft set-based models, particularly their inability to handle multiple experts’ opinions in a decision-making context. This paper’s major goal is to introduce the theory of fuzzy parameterized neutrosophic soft expert set theory. It also discusses the notion’s numerous related ideas and the basic operations on it, such as the complement, union, intersection, AND, and OR. The essential features of this idea are established, as are relevant rules such as De Morgan’s laws. A generalised algorithm is then used to apply the suggested idea of fuzzy parameterized neutrosophic soft expert sets in a decisionmaking situation. Moreover, in order to check the validity of the proposed algorithm, an example related to the choice of the area of building project using the decision-making method is presented. The suggested method provides reliable, reliable decision-making outcomes, and its enhanced capacity and dependability are confirmed by a robust comparison with earlier models.